Integrasi Sistem Pencegahan Penyebaran Covid 19 Pada Masa New Normal - Ahmad P Sardju; Idham A Djufri (Universitas Khairun, 2021)
Some important things that still have to be done when new normal for newspapers are at the entrance to the workplace, take temperature measurements using a thermogun, and before entering work, a Covid-19 Risk Self-Assessment is implemented to ensure that workers who will enter work are not infected with Covid- 19. Provide hand washing facilities (soap and running water). Then provide instructions for the location of the hand washing facilities. Then put up educational posters on how to wash hands properly. Given the importance of knowing body temperature and washing hands against the symptoms of the spread of the corona virus, this community service will create a system that integrates tools to support office activities during the new normal period. The integration of the system which will provide a device to record body temperature, a hand washer and a hand dryer, all work automatically